2011
DOI: 10.1155/2011/451694
|View full text |Cite
|
Sign up to set email alerts
|

The PD‐1/PD‐L1 (B7‐H1) Pathway in Chronic Infection‐Induced Cytotoxic T Lymphocyte Exhaustion

Abstract: Cytotoxic CD8 T lymphocytes (CTLs) play a pivotal role in the control of infection. Activated CTLs, however, often lose effector function during chronic infection. PD-1 receptor and its ligand PD-L1 of the B7/CD28 family function as a T cell coinhibitory pathway and are emerging as major regulators converting effector CTLs into exhausted CTLs during chronic infection with human immunodeficiency virus, hepatitis B virus, hepatitis C virus, and other pathogens capable of establishing chronic infections. Importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
94
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(96 citation statements)
references
References 78 publications
(130 reference statements)
2
94
0
Order By: Relevance
“…These cells display low levels of PD-1 in the presence of IL-2 and serve as an important source of antiviral T cells for the peripheral organs such as the liver. Based on these results and previous studies, [3][4][5][6][7] we speculated that the observed CD8 1 T-cell impairment in IFNAR 2/2 mice was partially attributable to insufficient hepatic IL-7. We found that hepatic IL-7 expression was significantly reduced in these mice following viral infection, and PD-1 levels on intrahepatic CD8 1 T cells were increased (Figure 5c and b).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…These cells display low levels of PD-1 in the presence of IL-2 and serve as an important source of antiviral T cells for the peripheral organs such as the liver. Based on these results and previous studies, [3][4][5][6][7] we speculated that the observed CD8 1 T-cell impairment in IFNAR 2/2 mice was partially attributable to insufficient hepatic IL-7. We found that hepatic IL-7 expression was significantly reduced in these mice following viral infection, and PD-1 levels on intrahepatic CD8 1 T cells were increased (Figure 5c and b).…”
Section: Discussionsupporting
confidence: 76%
“…High expression of, program death 1 (PD-1), an inhibitory receptor in the CD28 superfamily, is the hallmark of the exhausted CD8 1 T cells and contributes to the exhaustion of CD8 1 T cells during chronic viral infection. [3][4][5][6][7] In contrast to a relatively narrow range of PD-1 expression on activated T cells, its ligand, program death ligand 1 (PD-L1), was broadly expressed on a wide variety of cell types including hepatocytes. [8][9][10][11][12] Ligation of PD-1 and PD-L1 reduces the host immune reaction against pathogens and maintains immune tolerance.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, expansion of peripheral T H 17 cells during active MS, as well as enhanced frequencies of T H 17 cells in the cerebrospinal fluid during relapse, indicates that this population might be involved in disease exacerbation (8,9). Another study demonstrated increased frequencies of memory T H 17 cells in the peripheral blood of MS patients, which was further enhanced during relapse (10). In line with this, preliminary data from an ongoing double-blind, placebo-controlled, proof-of-concept trial with the IL-17A-neutralizing Ab secukinumab in patients with active MS support the pathogenic role of IL-17 in MS because secukinumab-treated patients exhibited a substantial reduction in the number of new inflammatory lesions revealed by magnetic resonance imaging (EudraCT number 2009-011626-34) (11).…”
mentioning
confidence: 98%
“…PD-1 has been identified as the canonical receptor for B7-H1 and is inducibly expressed on activated lymphocytes (21). Upon PD-1 binding, TCR-mediated signaling, a prerequisite for T cell activation, is suppressed, resulting in T cell anergy and tolerance (10,22,23).…”
mentioning
confidence: 99%
“…These improvements will require modifications both to the T cells themselves and to the tumor environment. For example, upregulation of PD-1 expression on T cells during chronic infections has been extensively reported and the PD-1 expression is associated with T cell exhaustion [140][141][142]; thus, in the future genetically modified T cells can be tested clinically in conjunction with checkpoint-blockade antibodies which have shown promising anti-tumor activity as a single agent against several cancers including HL [143][144][145][146]. Also a preclinical study has shown that epigenetic modifiers can enhance VST function [147].…”
Section: Discussionmentioning
confidence: 99%